COMPARATIVE ANALYSIS OF THE TRAINING OF LOW-RANKING BORDER GUARDS IN EDUCATIONAL INSTITUTION OF SLOVAKIA AND UKRAINE - Ольга Хамазюк; Ігор Блощинський (Збірник наукових праць Національної академії Державної прикордонної служби України. Серія: педагогічні науки, 2022)
The article reveals the content of the professional training of police officers of the Republic of Slovakia, in particular, providing the professional education to future low-ranking border guard specialists at the Secondary Vocational School of the Police Corps in the city of Kosice, which is the departmental training center for the Slovak border police. The educational curriculums and peculiarities of the training of future border police officers in the following specializations: “General Training” and “Border and Aliens Police” have been described. The peculiarities of providing the qualification training and training for professional development have been highlighted. It has been concluded that the content of the professional training of future border guard specialists of the Republic of Slovakia in departmental educational institutions allows to provide them with the basic knowledge, skills, abilities and competences necessary for carrying out professional activities in the border and migration service in accordance with the generally pted European standards for the training of border guards and the adopted Unified Program basic level for the training of border guard specialists (Common Core Curriculum), developed by the FRONTEX agency (European Border and Coast Guard Agency). A comparative analysis of the professional training of low-ranking border guards of the Police Corps of the Slovak Republic and junior personnel of the State Border Service of Ukraine has been conducted. It has been concluded that the content of the training of specialists of the above-mentioned countries has both common and different features. It has been revealed that the partial discrepancy is due to the peculiarity of the national legislation of Ukraine in the part that is related to the separation of the functions of state bodies performing their activities on the state border.